Analysis of Salivary Biomarkers in Periodontal Disease: Correlation of 8-OHdG with Clinical Parameters - Asmita Hamand (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Periodontal disease is characterized by inflammation and destruction of the tissues supporting the teeth, influenced by microbial infections, host immune response, and oxidative stress. 8-Hydroxydeoxyguanosine (8-OHdG) is a biomarker of oxidative DNA damage. This study investigates the correlation between salivary 8-OHdG levels and clinical parameters of periodontal disease, providing insights into oxidative stress's role in periodontal pathology. Methodology: The study included 100 subjects aged 30-60 years, divided into two groups: 50 with periodontal disease (test group) and 50 periodontally healthy individuals (control group). Subjects with systemic conditions, smokers, and those on antioxidant supplements were excluded. Unstimulated saliva samples were collected and stored at -80°C. 8-OHdG levels were measured using an ELISA kit. Clinical parameters were assessed by a calibrated periodontist, including CAL, PPD, BOP, PI, and GI. Data were analyzed using SPSS software, with Pearson correlation coefficient used to assess the relationship between salivary 8-OHdG levels and clinical parameters. A p-value of <0.05 was considered significant. Results: The test group showed significantly higher CAL, PPD, BOP, PI, and GI compared to the control group (p<0.05). The mean salivary 8-OHdG level was significantly higher in the test group (35.2 ng/mL) compared to the control group (12.6 ng/mL) (p<0.01). A significant positive correlation was observed between salivary 8-OHdG levels and clinical parameters: CAL (r = 0.62, p<0.01), PPD (r = 0.58, p<0.01), BOP (r = 0.47, p<0.05), PI (r = 0.53, p<0.05), and GI (r = 0.55, p<0.05).